Development of Real Estate Funds in Europe and Lithuania - Galinienė, Birutė; Bumelytė, Junona (Ekonomika, 2008)
Due to the growing economy in Lithuania as well its a rapid integration into the European Union and global markets, improvement of the investment process in real estate has been and will continue to be a topic of great interest. The article presents an analysis of the investment process in real estate. It aims at presenting a theoretical and practical evaluation of real estate as an investment object. To this end, the first part of the paper singles out the most important concepts related to real estate, compares real estate with other types of investment, analyses real estate in the investment portfolio. The second part explores the importance of real estate investment funds in order to ensure an efficient and expansive functioning of the investment market in the European Union and to expand the Lithuanian market of investment goods. It also investigates the legal basis and development of real estate funds in the European Union. Lithuanian legislation provided a possibility for real estate funds to operate only at the end of 2007: on 15 November 2007 a new edition of the Law on Collective Investment Undertaking of the Republic of Lithuania was adopted, stipulating a possibility for specialized funds to appear in Lithuania from 1 March 2008.